2021
DOI: 10.1002/pros.24114
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human prostate stromal cell growth and smooth muscle contraction by thalidomide: A novel remedy in LUTS?

Abstract: Background Medical treatment in benign prostatic hyperplasia targets prostate size to prevent disease progression, complications, and surgery, and prostate smooth muscle tone for rapid relief of lower urinary tract symptoms. Combination therapies are still required to target both at once. However, current medications are insufficient, due to an unfavorable balance between side effects and efficacy. The limited efficacy of α1‐blockers may be due to nonadrenergic mediators like endothelin‐1 and thromboxane A2 (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…These data coincide well and could be explained by the downregulation of BAX by the same treatment groups and explains the lack of cytotoxic effect of the three treatment regimens on WPMY-1 cells in the present MTT assay. Recently, similar results were obtained by Tamalunas et al, (2021), who studied how Thalidomide affected the biological functions of normal WPMY-1 stromal cells and the contraction of human smooth muscles. WPMY-1 cell growth was moderately affected by Thalidomide.…”
Section: The Efficiency Of Amygdalin and Doxorubicin Combination On H...supporting
confidence: 74%
“…These data coincide well and could be explained by the downregulation of BAX by the same treatment groups and explains the lack of cytotoxic effect of the three treatment regimens on WPMY-1 cells in the present MTT assay. Recently, similar results were obtained by Tamalunas et al, (2021), who studied how Thalidomide affected the biological functions of normal WPMY-1 stromal cells and the contraction of human smooth muscles. WPMY-1 cell growth was moderately affected by Thalidomide.…”
Section: The Efficiency Of Amygdalin and Doxorubicin Combination On H...supporting
confidence: 74%
“…In fact, a study has revealed that proliferation markers (PCNA and Ki67) could only be detected in glandular contents. Thus, the proliferation of mesenchymal cells can be assumed to originate from an epithelial-mesenchymal transition modulated by TGF-β [37,38]. SM plays a crucial role in the pathophysiology of BPH/LUTS despite the deterioration of the contractile apparatus and force generation in the enlarged prostate.…”
Section: Discussionmentioning
confidence: 99%
“…Lower urinary tract symptoms (LUTS), often secondary to BPH, are worrisome complication that place significant encumbrance on patients’ quality of life [ 2 ]. The increase in the number of periurethral epithelial and stromal cells characterizes BPH histopathologically due to the maladjustment of cell proliferation and death [ 3 ]. Although the molecular mechanism of BPH have been extensively studied, including a disequilibrium of sex hormone [ 4 ], stromal-epithelial interactions [ 5 ], cytokins [ 6 ], autoimmune [ 7 ] and oxidative stress (OS) [ 8 ], the exact pathogenesis remains unclear.…”
Section: Introductionmentioning
confidence: 99%